Investigating the common set of acoustic parameters in sexual orientation groups: A voice averaging approach. - Sven Kachel; André Radtke; Verena G Skuk; Romi Zäske; Adrian P Simpson; Melanie C Steffens (PLoS ONE, 2018)
While the perception of sexual orientation in voices often relies on stereotypes, it is unclear whether speech stereotypes and accurate perceptions of sexual orientation are each based on acoustic cues common to speakers of a given group. We ask if the stereotypical belief, that members of the same sexual orientation group share similar acoustic patterns, is accurate to some degree. To address this issue, we are the first to use a novel voice morphing technique to create voice averages from voices that represent extremes of a given sexual orientation group either in terms of actual or perceived sexual orientation. Importantly, averaging preserves only those acoustic cues shared by the original speakers. 144 German listeners judged the sexual orientation of twelve natural-sounding sentence stimuli, each representing an average of five original utterances. Half of the averages were based on targets' self-ratings of sexual orientation: On a 7-point Kinsey-like scale, we selected targets who were most typical for a certain sexual orientation group according to their self-identifications. The other half were based on extreme ratings by others (i.e., on speech-related sexual-orientation stereotypes). Listeners judged sexual orientation from the voice averages with above-chance accuracy suggesting 1) that the perception of actual and stereotypical sexual orientation, respectively, are based on acoustic cues shared by speakers of the same group, and 2) that the stereotypical belief that members of the same sexual orientation group share similar acoustic patterns is accurate to some degree. Mean fundamental frequency and other common acoustic parameters showed systematic variation depending on speaker gender and sexual orientation. Effects of sexual orientation were more pronounced for stereotypical voice averages than for those based on speakers' self-ratings, suggesting that sexual-orientation stereotypes exaggerate even those differences present in the most salient groups of speakers. Implications of our findings for stereotyping and discrimination are discussed.